Instrumental Activities of Daily Living Staging as a Possible Clinical Tool for Falls Risk Assessment in PM&R - Brown, Janice (2013)
OBJECTIVE: To determine if Instrumental Activity of Daily Living (IADL) Limitation Stages can distinguish among elderly, community-dwelling people with high likelihoods to have fallen once and more than once. DESIGN: Cross-sectional survey. SETTING: A nationally representative sample from the Second Longitudinal Study of Aging (LSOA II). PARTICIPANTS: Included were 7,401 community-dwelling persons 70 years of age and older. METHODS: The association of falling once and more than once within the past 12 months and five stages of increasing IADL limitation was explored using a multinomial logistic regression model controlling for demographics, education, perceived lack of home accessibility features, and health conditions. Samples proportions were weighted to reflect prevalence in the US population of 1994. MAIN OUTCOME MEASURES: Subjects' recall of fall history. There were three categories for this variable: no fall, falling once, and falling more than once in the past 12 months. RESULTS: Compared to IADL stage 0, the adjusted relative risk ratio of falling once peaked at IADL stage II at 2.0 (95% confidence interval (CI), 1.5-2.6), and those at IADL stage III had a relative risk ratio of 1.8 (95% CI, 1.3-2.6). The relative risk ratio of falling more than once was 2.1 (95% CI, 1.7-2.6), 4.0 (95% CI, 3.0-5.3), 3.7 (95% CI, 2.8-5.0), and 2.7 (95% CI, 1.5-4.9) for IADL stages I, II, III, and IV, respectively, treating IADL stage 0 as reference. CONCLUSIONS: IADL Limitation Stages could represent a powerful and practical tool for screening patients in the US elderly population according to falls risk. Clinical implementation and prospective testing for validation as a screening tool would be necessary.